Concept of the international programs monitoring the transboundary transport of pollution in the Black sea - Valery B. Mitko; Vladimir P. Degtyarev; Marina V. Minina (European Regional Science Association (ERSA), 2013)
The shelf of Black sea is rich to the lid posits of oil. The estimation of the reserves of the hydrocarbons only of western part of the Ukrainian shelf composes of 3,5 trln. tons of standard fuel, the oil-bearing sections of the Russian and Turkey shelf can contain to 1 billion tons of oil each. Tens of millions of tons of oil will be yearly obtained and unavoidably the part of this flow will arrive in sea.The special feature of waters of Black sea is the presence of hydrogen sulfide at the depths from 100 - 150 m. This factor substantially decreases the reliability and the period of the operation of underwater equipment. According to the estimation of specialists, the period of the service of the underwater part of the obtaining platforms under the conditions of Black sea can be reduced of up to 6 years instead of usual 20-25.The direction of flows is another special feature of Black sea waters. The existing circulatory flow along the shelf unavoidably will lead to the trans-border transfer of the pollution of sea water into the regions, where there is no oil production. First of all this relates to the coast of Bulgaria. The flow of the contaminated water from the Rumanian and Ukrainian sectors of the sea shelf, where the oil will be obtained on the large scales, can be mortally dangerous for nature of Bulgarian coast. In the prevailing situation it is necessary to initiate and to begin the coordinated actions of all Black Sea countries - Bulgaria, Rumania, Ukraine, Russia, Georgia, Turkey and Greece, directed toward the decrease of the threat of the pollution of Black sea during the industrial output of hydrocarbons from the sea shelf. It is obvious that each of the countries will be forced have the national system of monitoring the pollution of sea water in their sector of Black sea. Will be first of all claimed the systems of monitoring the trans-border transfer of the pollution of sea water, which make it possible to operationally and twenty-four hour determine the volume of the entered pollution, their composition and the hazard level.
Keywords: 330; shelf; Black sea; oil; gas; production; hydrocarbons; monitoring; trans-border; transfer; pollution; water; dangerous; regional; co-ordination; nature-saving; relates; coast